The Credit Rating Market - Options for Appropriate Regulation - Andreas Freytag; Martin Zenker (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2012)
The principal agent problem is one of the major issues of the credit rating agency market. Is it possible to solve the prevailing incentive problem of the market and contemporaneously satisfy the reputation demand of the investors? This paper presents an option for regulating the credit rating agency market more effectively. The market shall be coordinated through a central allocation office, which is acting as a mediator between both contractual parties. The paper develops a game theoretical approach that considers reputation as one of the most important aspects within the market. After analysing the status quo two policy options are discussed on a game theoretical basis. The main result is that the incorporation of a mediator, which awards the contracts based on a lottery drawing, would help to solve conflicts of interests. The incentive to inflate ratings decreases significantly. Moreover, rating shopping option becomes impossible. Two possible positive side effects for smaller CRAs and new incumbents are the increase of market share as well as reputation. Therefore, the market competition should be affected positively, too.
urn:nbn:de:gbv:27-20131126-103736-6
Keywords: G24; G28; D43; D82; 330; credit rating agencies; regulation; reputation; rating inflation; rating shopping